Triterpenoids from Ainsliaea henryi and their cytotoxic activities. (March 2016) - Zeng, Ren-Tao; Fang, Xin; Tian, Xin-Hui; Shi, Zhi-Ran; Dong, Xue-Yun; Zhuo, Zhi-Guo; Shen, Yun-Heng; Zhang, Wei-Dong
Graphical abstract: Highlights: Three new triterpenoids (1–3 ) were isolated from the aerial part of A. henryi. Compounds1 –3 were identified as cucurbitane-type triterpenes. Compounds2 and4 showed selective cytotoxicity against human tumor cells. Abstract: Three new cucurbitane-type triterpenoids, including (23 E )-cucurbita-3β-hydroxy-25-methoxy-5, 23-diene (1 ), (23 E )-cucurbita-3β-hydroxy-5, 23, 25-triene (2 ), and cucurbiata-3β-hydroxy-5, 25-dien-24-one (3 ), have been isolated with four known triterpenoids (4 -7 ) from the dried whole plants of Ainsliaea henryi. The chemical structures of compounds1 –3 were elucidated by 1D NMR ( 1 H, 13 C and DEPT), 2D NMR (COSY, HMBC, HSQC and NOESY) and HREIMS analyses. Among these compounds, compound3 exhibited strong cytotoxicity against human cancer cell lines MGC 803 (IC50  = 8.33 ± 0.94  μ M) and CCRF-CEM (IC50  = 4.34± 0.41  μ M), while compound6 significantly inhibited the proliferation of the A549 and HCT 116 cell lines with IC50 values of 2.14 ± 0.25 and 6.84 ± 0.39  μ M, respectively.